A 250-year periodicity in Southern Hemisphere westerly winds over the last 2600 years - C. S. M. Turney; R. T. Jones; C. Fogwill; J. Hatton; A. N. Williams; A. Hogg; Z. A. Thomas; J. Palmer; S. Mooney; R. W. Reimer (Climate of the Past, 2016)
Southern Hemisphere westerly airflow has a significant influence on the ocean–atmosphere system of the mid- to high latitudes with potentially global climate implications. Unfortunately, historic observations only extend back to the late 19th century, limiting our understanding of multi-decadal to centennial change. Here we present a highly resolved (30-year) record of past westerly wind strength from a Falkland Islands peat sequence spanning the last 2600 years. Situated within the core latitude of Southern Hemisphere westerly airflow (the so-called furious fifties), we identify highly variable changes in exotic pollen and charcoal derived from South America which can be used to inform on past westerly air strength. We find a period of high charcoal content between 2000 and 1000 cal. years BP, associated with increased burning in Patagonia, most probably as a result of higher temperatures and stronger westerly airflow. Spectral analysis of the charcoal record identifies a pervasive ca. 250-year periodicity that is coherent with radiocarbon production rates, suggesting that solar variability has a modulating influence on Southern Hemisphere westerly airflow. Our results have important implications for understanding global climate change through the late Holocene.